PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN DI PT. SECURINDO PACKATAMA INDONESIA JAKARTA SELATAN - Dyana Nur, Fina; Made Aryata, I (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine the effect of compensation and motivation on employee performance at PT Securindo Packatama Indonesia, South Jakarta. The method used is quantitative method. The sampling technique uses saturated sampling, which is as many as 40 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients and hypothesis tests. Test the hypothesis is assessed from the value of t count < t table or (1.432 < 2.024) It is also reinforced by a significance value of > 0.050 or (0.160 > 0.050). Thus, H0 is accepted and H1 is rejected, indicating that there is no significant effect between compensation and employee performance. The hypothesis test is assessed from the value of t calculated < t table or (2.017 <2.024) It is also reinforced by a significance value of > 0.050 or (0.051 >0.050). Thus, H0 is accepted and H2 is rejected, indicating that there is no significant effect between compensation and employee performance. The hypothesis test is assessed from the value of F count < F table or (2.179 < 3.259), this is also reinforced by significance > 0.050 or (0.127 > 0.050). Thus, H0 is accepted and H3 is rejected, indicating that there is no simultaneous significant effect between compensation and motivation on employee performance.